1988
DOI: 10.1002/bjs.1800750106
|View full text |Cite
|
Sign up to set email alerts
|

Results of resection of gastric cancer extending to adjacent organs

Abstract: We report the late results of resection in 281 patients with gastric carcinoma extending to adjacent organs. In 92 without incurable factors (peritoneal dissemination, liver metastasis and widespread nodal involvement) the 5-year survival rate was 36.7 per cent in those treated by gastrectomy and complete removal of the invaded organ. This value is significantly higher than the 17.4 per cent recorded in those undergoing gastrectomy alone or with incomplete removal of the invaded organs (P less than 0.05). In 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 8 publications
2
52
0
3
Order By: Relevance
“…These findings suggest that the effectiveness of complete excision is related not so much to multiple organ involvement and the presence of lymph node metastasis as it is to the presence of incurable factors such as peritoneal metastasis and liver metastasis. Korenaga et al [2] have also recommended complete excision of invaded organs, irrespective of the number of organs or the site of organs involved, provided that there is no evidence of incurable factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that the effectiveness of complete excision is related not so much to multiple organ involvement and the presence of lymph node metastasis as it is to the presence of incurable factors such as peritoneal metastasis and liver metastasis. Korenaga et al [2] have also recommended complete excision of invaded organs, irrespective of the number of organs or the site of organs involved, provided that there is no evidence of incurable factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the majority of patients with gastric carcinoma the primary lesion is confined to the gastric wall, in approximately 10% to 20% of patients who undergo resection, the tumor has crossesd the serosal layer and extends to adjacent organs [1,2]. In such patients, extensive en-bloc resection of the invaded organs is required [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic lymph node dissection of more than D2 resection was carried out (Maehara et al, 1992). Complete excision of invaded organs was done irrespective of the number of sites on the organs, when there was no evidence of incurable factors such as peritoneal dissemination, liver metastasis and widespread nodal involvement (Korenaga et al, 1988a). All patients were examined clinically and pathologically with respect to the factors given in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Iriyama et al [15] reported the highest 5-year survival rate of 46% after extended gastric resection with adjacent organs in patients with T4 gastric cancer. And Korenaga et al [16] reported that the 5-year survival was 36.7% for those who underwent radical resection of adjacent organs and 17.4% for those who underwent palliative resection of adjacent involved organs. Ozaki et al [17] and others [16] have found that an aggressive approach to resection of the stomach with the body and tail of the pancreas or PD and right hemicolectomy can lead to an acceptable 5-year survival rate of 29%.…”
Section: Discussionmentioning
confidence: 99%